Laparoscopic Transabdominal Pre-Peritoneal (Tapp) Procedure for Inguinal Hernia: Our Experience in a Developing Country. - Pankaj S,; Pankaj D,; Ashwani K,; Vijay K,; Anand M, (Department of Surgery, UKM Medical Centre, 2014)
The aim of study was to observe the outcome and limitations of laparoscopic hernia repair in developing country. Hundred patients of inguinal hernia who underwent Laparoscopic Transabdominal Pre-Peritoneal (TAPP) hernioplasty were observed for hospital stay, pain and post operative recovery. Mean operative time was 76.95 minutes. Only 12 patients developed complications in form of seroma formation (8 patients) and wound infection (4 patients). All patients were discharged within 48 hours. Mean time of return to work was 12.2 days. Hence, it is concluded that except for its high cost, the procedure is safe and allows less hospital stay and early return to work.